Follow Me to Hell : McNelly's Texas Rangers and the Rise of Frontier Justice - Clavin, Tom, 1954- (New York : St. Martins Press, 2023)
"Tom Clavins Follow Me to Hell is the explosive true story of how legendary Ranger Leander McNelly and his men brought justice to a lawless Texan frontier. In turbulent 1870s Texas, the revered and fearless Ranger Leander McNelly led his men in one dramatic campaign after another, throwing cattle thieves, desperadoes, border ruffians, and other dangerous criminals into jail or, if thats how they wanted it, six feet under. They would stop at nothing in pursuit of justice, even sending 26 Rangers across the border to retrieve stolen cattle--taking on hundreds of Mexican troops with nothing but their Sharps rifles and six-guns. The nation came to call them "McNellys Rangers." Set against the backdrop of 200 years of thrilling Texas Rangers history, this page-turner takes readers into the tough life along the Texas border that was tamed by a courageous, yet doomed, captain and his team of fearless men. It was one hell of a ride!"--
"Texian devils!" -- Luckless liberators -- The long republic -- A Connecticut Yankee -- The empresario -- The "Magna Carta" -- An inkling of independence -- Unlearned lessons -- Austin behind bars -- "Come to our aid" -- "How do you like that answer?" -- Looting and shouting -- "Hurry on!" -- "Victory purchased with blood" -- Take the fight south -- From bad to worse -- The finest company -- "My men evinced no dismay" -- "Boys, fight to the last!" - - Invading Comancheria -- "Walking whiskey keg" -- Gettysburg of the west -- "Coolness and courage" -- Frontier forces -- "True to his colors" -- Farmer and father -- No book to stop this bullet -- Follow the money -- Another long and bloody war -- Quick with a gun -- "A perfect reign of terror" -- The peacekeepers -- Reporters and rangers -- Patrolling the Nueces strip -- "You must be the judge" -- Emperor McNelly -- "Got you now!" -- "Master of the situation" -- "The jaws of death" -- "Kill all you see" -- Rio Grande standoff -- "Death squad" -- Captain McNelly goes to Washington -- "This rash young man" -- "Two best pistol fighters in Texas" -- The new lieutenant -- "The brave who sink to rest".
Keywords: McNelly, Leander H., -- 1843 or 1844-1877.; Police, State -- Texas; Biography; Frontier and pioneer life -- Texas; Texas -- History -- 1846-1950.; History